Osmoregulation and the Hypothalamic Supraoptic Nucleus: From Genes to Functions - Mecawi, André Souza; Varanda, Wamberto Antonio; da Silva, Melina Pires (Frontiers in Physiology, 2022)
Due to the relatively high permeability to water of the plasma membrane, water tends to equilibrate its chemical potential gradient between the intra and extracellular compartments. Because of this, changes in osmolality of the extracellular fluid are accompanied by changes in the cell volume. Therefore, osmoregulatory mechanisms have evolved to keep the tonicity of the extracellular compartment within strict limits. This review focuses on the following aspects of osmoregulation: 1) the general problems in adjusting the “milieu interieur” to challenges imposed by water imbalance, with emphasis on conceptual aspects of osmosis and cell volume regulation; 2) osmosensation and the hypothalamic supraoptic nucleus (SON), starting with analysis of the electrophysiological responses of the magnocellular neurosecretory cells (MNCs) involved in the osmoreception phenomenon; 3) transcriptomic plasticity of SON during sustained hyperosmolality, to pinpoint the genes coding membrane channels and transporters already shown to participate in the osmosensation and new candidates that may have their role further investigated in this process, with emphasis on those expressed in the MNCs, discussing the relationships of hydration state, gene expression, and MNCs electrical activity; and 4) somatodendritic release of neuropeptides in relation to osmoregulation. Finally, we expect that by stressing the relationship between gene expression and the electrical activity of MNCs, studies about the newly discovered plastic-regulated genes that code channels and transporters in the SON may emerge.